2020
DOI: 10.1080/24749508.2020.1742510
|View full text |Cite
|
Sign up to set email alerts
|

Tree carbon stock and its relationship to key factors from a tropical hill forest of Tamil Nadu, India

Abstract: The present study was carried out to understand the relationship of tree carbon stock to key factors such as species richness, density and altitude, in Pachaimalai tropical hill forest located in Tamil Nadu, India. The study area (PTHF) was parted into 24 6.25 km × 6.25 km grids, and at each grid, all live trees ≥30 cm girth at breast height were recorded from a randomly placed 0.5 ha transect. The total carbon stock estimated for the PTHF ranged from 4.79 to 119.00 t ha −1 (n = 24). The species richness, dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
5
9
0
2
Order By: Relevance
“…The current study found carbon stock in PJS and SGS to be 32 ± 20.6 tons/ha and 27.3 ± 22.4 tons/ha, respectively. The findings of the current study are in line with a recent study 83 on deciduous forests (denoted as Sacred Groves Stands—Outside the protected area, Pachaimalai tropical hill forest) in central Tamil Nadu in which mean carbon stock ranged between 7.6 t ha -1 to 23.4 t ha -1 . While in the case of Prosopis juliflora stands, no authenticated information on carbon stock in India is reported, but a study in Ethiopia recorded it to be in the range from 85.8 ± 4.7 Mg/ha (in dense thickets) to 48.2 ± 4.4 Mg/ha (in sparse thickets) 84 .…”
Section: Discussionsupporting
confidence: 90%
“…The current study found carbon stock in PJS and SGS to be 32 ± 20.6 tons/ha and 27.3 ± 22.4 tons/ha, respectively. The findings of the current study are in line with a recent study 83 on deciduous forests (denoted as Sacred Groves Stands—Outside the protected area, Pachaimalai tropical hill forest) in central Tamil Nadu in which mean carbon stock ranged between 7.6 t ha -1 to 23.4 t ha -1 . While in the case of Prosopis juliflora stands, no authenticated information on carbon stock in India is reported, but a study in Ethiopia recorded it to be in the range from 85.8 ± 4.7 Mg/ha (in dense thickets) to 48.2 ± 4.4 Mg/ha (in sparse thickets) 84 .…”
Section: Discussionsupporting
confidence: 90%
“…Findings of the current study are in line with recent previous study at deciduous forests (i.e. denoted as Sacred Groves Stands -Outside the protected area) across central Tamil Nadu in which mean carbon stock, ranged between 7.6 t ha − 1 to 23.4 t ha − 1(Pragasan, 2022). While in the case of Prosopis juli ora stands, no authenticated information on carbon stock in India was reported, but a study in Ethiopia had recorded in the range from 85.8 ± 4.7 Mg/ha (in dense thickets) to 48.2 ± 4.4 Mg/ha (in sparse thickets)(Birhane et al, 2017).…”
supporting
confidence: 92%
“…According to [73] there is no substantial association between carbon stock and the density of tree species. [29] Found similar results in tropical forests in India, as well as a negative association in community forests in Nepal.…”
Section: Carbon Concentration and Density Of Tree Species In The Different Forest Zonementioning
confidence: 99%